Impact of Emotional Intelligence on Aggressive Fantasies and Empathy Among Adults - Yousra Khan; Arfa Ijaz; Amina Safdar; Dr. Sajid Mahmood Alvi; Aamna Bibi (International Journal of Business and Economic Affairs, 2024)
The study aimed to explore the influence of emotional intelligence on adolescents’ tendencies towards aggressive fantasies and empathy. A sample of 300 individuals (147 males and 153 females) was selected for the study. Initially, a weak correlation was found betweenemotional intelligence and aggression, suggesting that higher emotional intelligence does not necessarily lead to reduced levels of aggression in adolescents. Conversely, a positive correlation was observed between emotional intelligence and empathy, indicating that adolescents with higher emotional intelligence tend to demonstrate greater empathy towards others. Furthermore, the research identified a causal relationship between emotional intelligence and aggressive fantasies. Gender differences were also observed in emotional intelligence, empathy, and tendencies towards aggressive fantasies.